Passively Active Investing – A Five Year Test - Haber, Jeffry (Journal of Applied Business and Economics, 2020)
This paper took five years of the Council on Foundations-Commonfund study of Foundations and using the average asset allocation replaced the active managers with ETFs. The ETFs comprised the “replacement portfolio.” Over the five years the active portfolio outperformed the replacement portfolio in four of the five years. The five-year return of the actively managed portfolio was 8.1% versus 4.8% for the replacement portfolio. The ETFs chosen that replaced the managers were similar strategies and chosen based on having a low expense ratio. No review of past performance was done. During the five years poorly performing ETFs were not replaced.